Clinical Outcomes, Health Care Costs and Prognostic Factors for Total Knee Arthroplasty: A Multilevel Analysis of a National Cohort Study Using Administrative Claims Data - Buitrago, Giancarlo; Ortiz, Jorge R.; Camacho, Felipe (The Journal of Knee Surgery, 2020)
Total knee arthroplasty (TKA) is one of the most frequent orthopaedic surgeries. The purpose of this study was to determine the 30-day postoperative mortality rate, total episode-of-care costs, and prognostic factors associated with these outcomes, for adult patients who underwent TKA in Colombia's contributory health care system. A retrospective cohort study of all adult patients enrolled in Colombia's contributory health system, who underwent TKA between January 1, 2012 and November 30, 2015 was performed. Thirty-day postoperative mortality rates, 30-day ICU admissions rates, 30-day hospital readmission rates, 1-year arthroplasty revision rates, and total episode-of-care costs were estimated. Multilevel, generalized linear models were generated, to determine the prognostic factors associated with outcomes presented. A total of 12,453 patients were included. The 30-day mortality rate was 0.13 per 100 surgeries and the ICU admissions rate at 30 days postoperative was 4.44 per 100 surgeries. The 30-day hospital readmission rate was 4.28 per 100 surgeries and the 1-year arthroplasty revision rate was 1.22 per 100 surgeries. The prognostic factors associated with mortality were age, Charlson Index, and type of insurer. The prognostic factors associated with hospital readmission were age category, Charlson Index, and geographic region; younger age and higher Charlson Index were found to be associated with a higher 1-year arthroplasty revision rate. The median of total episode-of-care costs was USD$ 6,190.07 (interquartile range: 2,299–7,282). The multivariate model found that age, the Charlson Index, the Atlantic region, and type of insurer were associated with the costs incurred by the health system. For patients undergoing TKA in Colombia, age, the Charlson Index, insurers, and geographic region are associated with mortality, ICU admissions, 30-day hospital readmissions, 1-year arthroplasty revisions, and total costs incurred by the health system.
Keywords: total knee arthroplasty; costs; developing country; Charlson Index; Likelihood rate